Optical in situ monitoring during the synthesis of halide perovskite solar cells reveals formation kinetics and evolution of optoelectronic properties. Issue 20 (18th May 2020) - Suchan, Klara; Just, Justus; Becker, Pascal; Unger, Eva L.; Unold, Thomas
Abstract : Optical in situ monitoring tracks crystallization and optoelectronic properties of halide perovskites during growth in a glovebox environment. Abstract : The formation mechanism and the evolution of optoelectronic properties during annealing of chlorine-derived methylammonium lead iodide (MAPbI3− x Cl x ) are investigated in detail combining in situ and ex situ optical and structural characterization. Using in situ optical reflectometry we are able to monitor the evolution of the MAPbI3− x Cl x phase as a function of time and processing temperature. The formation kinetics is fitted using an improved Johnson–Mehl–Avrami–Kolmogorov model and a delayed formation of MAPbI3− x Cl x is found when chlorine is present in the precursor. This is verified by X-ray diffraction and X-ray fluorescence measurements. From absolute photoluminescence measurements we determine the implied V oc during film formation, which exhibits a maximum at a specific time during the annealing process. In conjunction with ex situ time-resolved photoluminescence we deduce a decrease in the net doping density for increased annealing times, while the minority carrier lifetime stays constant. We thus demonstrate the potential of in situ optical spectroscopy to monitor and tailor the electronic properties of hybrid perovskites directly during film growth, which can be easily applied to different growth recipes and synthesis environments.